Is There a Neurologist in the House? A Summary of the Current State of Neurovascular Rotations for Emergency Medicine Residents. (12th November 2018) - Wira, Charles R.; Madsen, Tracy E.; Chang, Bernard P.; Nomura, Jason T.; Marcolini, Evie; Gentile, Nina T.; Schreyer, Kraftin E.; Merck, Lisa H.; Siket, Matthew; Greenberg, Karen; Zammit, Christopher G.; Jauch, Edward C.; et al.
Abstract: Objectives: Neurovascular and neurocritical care emergencies constitute a leading cause of morbidity/mortality. There has been great evolution in this field, including but not limited to extended time‐window therapeutic interventions for acute ischemic stroke. The intent of this article is to evaluate the goals and future direction of clinical rotations in neurovascular and neurocritical care for emergency medicine (EM) residents. Methods: A panel of 13 board‐certified emergency physicians from the Society for Academic Emergency Medicine (SAEM) neurologic emergencies interest group (IG) convened in response to a call for publications—three with fellowship training/board certification in stroke and/or neurocritical care; five with advanced research degrees; three who have been authors on national practice guidelines; and six who have held clinical duties within neurology, neurosurgery, or neurocritical care. A mixed‐methods analysis was performed including a review of the literature, a survey of Council of Emergency Medicine Residency Directors (CORD) residency leaders/faculty and SAEM neuro‐IG members, and a consensus review by this panel of select neurology rotations provided by IG faculty. Results: Thirteen articles for residency neurovascular education were identified: three studies on curriculum, three studies evaluating knowledge, and seven studies evaluating knowledge after an educational intervention. Intervention outcomes included the ability to recognize and manage acute strokes, manage intracerebral hemorrhage, calculate National Institutes of Health Stroke Scale (NIHSS), and interpret images. In the survey sent to CORD residency leaders and neuro‐IG faculty, response was obtained from 48 programs. A total of 52.1% indicated having a required rotation (6.2% general neurology, 2% stroke service, 18.8% neurologic intensive care unit, 2% neurosurgery, 22.9% on a combination of services). The majority of programs with required rotations have a combination rotation (residents rotate through multiple services) and evaluations were positive. Conclusions: Variability exists in the availability of neurovascular/neurocritical care rotations for EM trainees. Dedicated clinical time in neurologic education was beneficial to participants. Given recent advancements in the field, augmentation of EM residency training in this area merits strong consideration.